2000
DOI: 10.1385/bter:73:1:1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Toxicity of Rare-Earth Elements on Human Beings : Implications of Blood Biochemical Indices in REE-high Regions, South Jiangxi

Abstract: Blood analyses for rare-earth element (REE)-high background regions in South Jiangxi show that the population averages of many of the biochemical indices deviate markedly from normal values in the normal region. These deviations are thought to be caused by prolonged intake of REE through food chains in view of that the toxicity of other harmful metals such as Pb and Cd can be neglected because of their insignificant amounts in the environment. In comparison with the normal region, blood biochemical indices abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(30 citation statements)
references
References 18 publications
0
29
0
1
Order By: Relevance
“…The total REE concentrations in stream water decreased due to sorption by and/or coprecipitation with soil components (Medas et al 2013) during downward transport. It is now well known that intake of REEs over a long period has harmful effects on human liver and kidneys, as well as negative effects on immunity (Zhang et al 2000). When compared with the normal region, blood biochemical indices of human beings were abnormal in the REE high regions, and the effects of REE on males were a one-way irreversible process (Zhang et al 2000).…”
Section: La Ce Pr Nd Sm Eu Gd Tb Dy Ho Er Tm Yb Lumentioning
confidence: 99%
See 1 more Smart Citation
“…The total REE concentrations in stream water decreased due to sorption by and/or coprecipitation with soil components (Medas et al 2013) during downward transport. It is now well known that intake of REEs over a long period has harmful effects on human liver and kidneys, as well as negative effects on immunity (Zhang et al 2000). When compared with the normal region, blood biochemical indices of human beings were abnormal in the REE high regions, and the effects of REE on males were a one-way irreversible process (Zhang et al 2000).…”
Section: La Ce Pr Nd Sm Eu Gd Tb Dy Ho Er Tm Yb Lumentioning
confidence: 99%
“…It is now well known that intake of REEs over a long period has harmful effects on human liver and kidneys, as well as negative effects on immunity (Zhang et al 2000). When compared with the normal region, blood biochemical indices of human beings were abnormal in the REE high regions, and the effects of REE on males were a one-way irreversible process (Zhang et al 2000). Despite the absence of related permissible limits for REEs in different water quality standards in China, much attention should be paid to the local residents' health risk caused by drinking water.…”
Section: La Ce Pr Nd Sm Eu Gd Tb Dy Ho Er Tm Yb Lumentioning
confidence: 99%
“…Although Chinese scientists have studied the health impact of REE exposure [12][13][14][15][16], suitable methods for the analysis of Sc in biological materials and biological indicators for Sc exposure are still unavailable. Increasing demand for REEs by industry expansion implies greater risk of exposure to REEs requiring additional research to assess potential health effects derived from such exposure.…”
mentioning
confidence: 99%
“…Similarly, Rambeck and Wehr (2005) indicated that REE may possess certain antibacterial properties and promote animal growth by selectively influencing the development of bacterial species in the gastrointestinal tract. Moreover, Zhang et al (2000) and Liu et al (2004) demonstrated that REE was able to inhibit the growth of several bacteria dose-dependently. In the present study, high dose of REE (300 mg/kg) supplementation led to no further improvement of total digestibility, and in situ ruminal degradation confirmed that REE modulate the digestive microorganisms or enzymes in a dosedependent manner.…”
Section: Effect Of Rare Earth Elements In Sheepmentioning
confidence: 99%